Synthesis and Characterization of Cocozone Oil as Skin Care Ingredient - ., Enjarlis; Handayani, Sri; Anwar, Yenny (International Journal of Engineering and Technology, 2018)
Cocozone Oil (CCO) is one of the ozonated oils, obtained by the ozonation process of Virgin Coconut Oil (VCO), that can be used as a material for skin care products. The purpose of this study was to determine: (1) the optimum time and ozone dose for CCO synthesis from VCO using ozonation; (2) the changes in physico-chemical properties of the oil; (3) the change in saturated-unsaturated fatty acids content and the existence any new substances in the CCO. The ozonation of VCO was carried out for 25 hours, with monitoring at the intervals of 4, 8, 12, 16, 20 and 25 hours, at a constant temperature (25 °C) with an ozone flow of 0.25 g/hr. From this study it can be concluded that: (1) The optimal time or dose of ozone required for the synthesis of CCO from VCO through the ozonation process was 25 hours or equivalent to 0.0208 gr O3/ml VCO, (2) Physico-chemical characteristics of the CCO produced: resulting acid value (AV) was 2.71 mg/gram i.e. an increase of 630%; the peroxide value (PV) obtained was 238,77 mgrek/kg i.e. increase  of 3,453 %; the Iodine value (IV) was 0 (zero) i.e. a decrease of 100%; and, the viscosity was 13.30 centipoice i.e. it rose 116%; (3) the total content of saturated fatty acid increased by 3.34%  whereas the unsaturated fatty acid decreased by 98.83; and based on the analysis results of 13C and 1H NMR spectra, the resultant CCO contains a new substance, that is aldehydes.